2006
DOI: 10.1158/0008-5472.can-05-1988
|View full text |Cite
|
Sign up to set email alerts
|

Restoring E-Cadherin Expression Increases Sensitivity to Epidermal Growth Factor Receptor Inhibitors in Lung Cancer Cell Lines

Abstract: The epidermal growth factor receptor (EGFR) is overexpressed in the majority of non-small cell lung cancers (NSCLC). EGFR tyrosine kinase inhibitors, such as gefitinib and erlotinib, produce 9% to 27% response rates in NSCLC patients. E-Cadherin, a calcium-dependent adhesion molecule, plays an important role in NSCLC prognosis and progression, and interacts with EGFR. The zinc finger transcriptional repressor, ZEB1, inhibits E-cadherin expression by recruiting histone deacetylases (HDAC). We identified a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
354
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(381 citation statements)
references
References 43 publications
24
354
3
Order By: Relevance
“…17,19,20,31 Moreover, E-cadherin has been proposed as a biomarker for therapies, such as EGFR tyrosine kinase activity inhibitors or other molecules interfering with EGFR signaling. 18,32 Our study data also suggest that E-cadherin expression could be a clinically relevant biomarker for TK/GCV therapy. …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…17,19,20,31 Moreover, E-cadherin has been proposed as a biomarker for therapies, such as EGFR tyrosine kinase activity inhibitors or other molecules interfering with EGFR signaling. 18,32 Our study data also suggest that E-cadherin expression could be a clinically relevant biomarker for TK/GCV therapy. …”
Section: Discussionsupporting
confidence: 54%
“…The central role of E-cadherin in modulating the response to a variety of different antitumoral therapies, such as, EGFR-targeted treatment, 18,19 or the chemotherapeutic agents taxol and etoposide, 17,20 has been shown. However, the ability of E-cadherin to enhance TK/GCV cytotoxicity is reported for the first time in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small cell lung cancer, E-cadherin has an important function in prognosis and progression and interacts with EGFR. In this neoplasia, E-cadherin and ZEB1 expression correlate with sensitivity to the EGFR inhibitor genitinib (Witta et al, 2006). Similarly, colorectal and pancreatic cell lines with mutated or no E-cadherin are also insensitive to the EGFR inhibitor erlotinib (Buck et al, 2007).…”
Section: Mutual Regulation Of Sprouty-2 and E-cadherinmentioning
confidence: 88%
“…It is reported that patients with phospho AKTpositive tumours had a better response rate, disease control rate, and time to progression by gefitinib treatment (Cappuzzo et al, 2004). Expression of E-cadherin, a calcium-dependent adhesion molecule, has been related to sensitivity to gefitinib (Witta et al, 2006). These lines of evidence clearly indicate that comprehensive analyses of molecular biomarkers should be carried out in conjunction with clinical trials of EGFR inhibitors.…”
Section: Biomarker For Egfr-tkimentioning
confidence: 97%